Nature and Role of Qualitative Market Research: An Alternative or a Complimentary Approach? - Batra, Ankita (Indian Journal of Marketing, 2014)
The purpose of this paper was to carry out an extensive review of qualitative market research and quantitative market research and comprehensively compare and contrast similarities and differences between the two. An extensive study of the concepts and practices of qualitative market research and quantitative market research is carried out from the literature. The findings identified that both research methodologies are very distinct based on their goals and techniques. A triangulation approach combining the two can lead to synergy in the research process. Another area where a need for cross fertilization is highlighted is between academic and applied practices to narrow the academic research divide.